Influence of Micropatterned Grill Lines on Entamoeba histolytica Trophozoites Morphology and Migration - Sierra-López, Francisco; Baylón-Pacheco, Lidia; Espíritu-Gordillo, Patricia; Lagunes-Guillén, Anel; Chávez-Munguía, Bibiana; Rosales-Encina, José L. (Frontiers in Cellular and Infection Microbiology, 2018)
Entamoeba histolytica, the causal agent of human amoebiasis, has two morphologically different phases: a resistant cyst and a trophozoite responsible for the invasion of the host tissues such as the colonic mucosa and the intestinal epithelium. During in vitro migration, trophozoites usually produce protuberances such as pseudopods and rarely filopodia, structures that have been observed in the interaction of trophozoites with human colonic epithelial tissue. To study the different membrane projections produced by the trophozoites, including pseudopods, filopodia, uropods, blebs and others, we designed an induction system using erythrocyte extract or fibronectin (FN) in micropatterned grill lines (each micro-line containing multiple micro-portions of FN or erythrocyte extract) on which the trophozoites were placed in culture for migration assays. Using light, confocal, and scanning electron microscopy, we established that E. histolytica trophozoites frequently produce short and long filopodia, large retractile uropods in the rear, pseudopods, blebs and others structures, also showing continuous migration periods. The present study provides a simple migration method to induce trophozoites to generate abundant membrane protrusion structures that are rarely obtained in normal or induced cultures, such as long filopodia; this method will allow a –better understanding of the interactions of trophozoites with FN and cell debris. E. histolytica trophozoites motility plays an important role in invasive amoebiasis. It has been proposed that both physical forces and chemical signals are involved in the trophozoite motility and migration. However, the in vivo molecules that drive the chemotactic migration remain to be determined. We propose the present assay to study host molecules that guide chemotactic behavior because the method is highly reproducible, and a live image of cell movement and migration can be quantified.